The ratio of extracellular water to total body water serves as a potential predictor of diabetic peripheral neuropathy in patients - Chen, Lu; Zhang, Junli; Xu, Zhenghui; Huang, Mengting; Hua, Fei; Fu, Yu (Frontiers in Endocrinology, 2025)
BackgroundDiabetic peripheral neuropathy (DPN), a common chronic complication of type 2 diabetes mellitus (T2DM), lacks simple biomarkers for early monitoring. This study aimed to explore the association between the ratio of extracellular water to total body water (ECW/TBW) and DPN.MethodsA total of 707 T2DM patients recruited from the Third Affiliated Hospital of Soochow University were included in this cross-sectional study. Multivariate logistic regression analyses were performed to assess the association between the ECW/TBW ratio and DPN after adjusting. Receiver operating characteristic (ROC) curves were used to evaluate the predictive value of the ECW/TBW ratio for DPN.ResultsThe risk of DPN is related significantly with ECW/TBW ratio by multivariate logistic regression analyses, especially the ECW/TBW ratio of arms, trunk, and legs. And the ECW/TBW ratio can not be a indicator to predict the DPN rick of whose BMI is above 28kg/m². Besides, adding the ECW/TBW ratio to the baseline model gained a positive change in the integrated discrimination improvement and continuous net reclassification improvement. The area under the curve (AUC) of ECW/TBW (AUC:0.678) was higher than that of Neutrophil-to-Lymphocyte Ratio (NLR, AUC:0.620) and Platelet-to-Lymphocyte Ratio (PLR, AUC:0.568).ConclusionsThe ratio of ECW/TBW exhibits a potential predictive capacity for DPN and better than NLR and PLR in T2DM patients with BMI <28 kg/m².